A Shell Script – Cleaner - Tarani, H; Vinchurkar, T; Syeda, R (International Journal of Computer Sciences and Engineering, 2025)
In Linux system the cleaning of all the cache and temporary memory is a complex task done by command line. Memory management in any operating system is considered as complex task. In Linux system the major hectic task is to manage & free the unnecessary memory usage of applications. By developing this tool we are trying to reduce the overhead of Linux user for better management of memory resources. Now the problem is to enlist the memory usage of all installed applications, for that we developed a module which enlists the installed applications. A shell script cleaner is an interactive tool which consist of multiple modules for different distribution. Every module consists of distribution specific commands and their dependencies over the memory structure. This tool provides an interface to enlist the memory usage and delete cache memory as well as other alternatives of cache memory using the menu driven interface. By prefixing a word shell script make this tool very resourceful and automated. Almost every automation task in Linux system are done via shell scripting. Thus results in better memory management and cache cleaning techniques.